2020
DOI: 10.1088/2516-1075/ab9f94
|View full text |Cite
|
Sign up to set email alerts
|

Hartree theory calculations of quasiparticle properties in twisted bilayer graphene

Abstract: A detailed understanding of interacting electrons in twisted bilayer graphene (tBLG) near the magic angle is required to gain insights into the physical origin of the observed broken symmetry phases. Here, we present extensive atomistic Hartree theory calculations of the electronic properties of tBLG in the (semi-)metallic phase as function of doping and twist angle. Specifically, we calculate quasiparticle properties, such as the band structure, density of states (DOS) and local density of states (LDOS), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 70 publications
3
73
0
Order By: Relevance
“…Figure 5 shows that the extra electron fill the flat states and align the Dirac point with the Fermi energy. Small modifications in the electronic band structure as a result of new electrostatic contributions is observed, similarly to other twisted multilayer systems [68][69][70][71].…”
Section: Impact Of Chemical Dopingmentioning
confidence: 69%
“…Figure 5 shows that the extra electron fill the flat states and align the Dirac point with the Fermi energy. Small modifications in the electronic band structure as a result of new electrostatic contributions is observed, similarly to other twisted multilayer systems [68][69][70][71].…”
Section: Impact Of Chemical Dopingmentioning
confidence: 69%
“…where n j denotes the occupancy of the p z orbital on atom j and n is the average occupancy [48]. Also, W i j denotes the screened Coulomb interaction between electrons at τ i and τ j [49]. In principle, V (τ i ) must be determined self-consistently, but it has been shown [46,47,49] that the resulting potential is accurately described by…”
Section: Methodsmentioning
confidence: 99%
“…It is well known, however, that long-ranged interactions play an important role in tBLG. Using Hartree theory, several groups [46][47][48][49][50] demonstrated that long-ranged interactions result in significant changes of the electronic structure which depend sensitively on doping and twist angle. In particular, Hartree interactions result in a flattening of the doped bands (in addition to the band flattening induced by twisting) [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…4a,c,e). This signals that the shape of dispersive pockets within the flat bands do not change significantly as flatter parts of the bands are deformed due to interactions 30,31 . Taken together, these observations put strict restrictions on the overall band structure of the MATBG and provide guidence for further theoretical modeling.…”
mentioning
confidence: 99%
“…Some of the early observations in MATBG remain poorly understood-e.g., the appearance of four-fold degenerate LLs around charge neutrality 1 instead of eight-fold as expected from the presence of eight degenerate Dirac cones of the two stacked monolayers, and anomalously large bandwidth (∼ 40 meV) of the flat band [19][20][21][22] deviating from the 5 − 10 meV widths expected from continuum models 10 . This is largely due to difficulties in band structure calculations that incorporate all relevant effects such as electronic correlations [30][31][32] , strain 33 , and atomic reconstruction 34 . In particular, several mechanisms were proposed to explain the origin of four-fold LLs formed at charge neutrality 33,35,36 but to date there is no general consensus.…”
mentioning
confidence: 99%